Effects of Construction Sequences and Volume Loss on Perpendicularly Crossing Tunnels - Yanwei Zang; Penglu Gan; Jia-jia Yan; Shiming Liu; Zihai Yan (Advances in Civil Engineering)
The number of constructed tunnels has been gradually increasing for the past decades due to rapid development in urban areas. However, the soil-structure interaction problems arising from perpendicularly crossing tunnels attract relatively little research attention in the past. In this study, six three-dimensional finite element analyses were conducted to simulate tunnel excavation nearby a perpendicularly crossing existing tunnel, in an attempt to investigate the effects of construction sequences on cross-cutting tunnels. The hypoplastic constitutive model for sand is adopted in the numerical analysis to consider the soil small-strain stiffness. Computed results are presented and discussed in terms of ground surface settlement, displacement and deformation of the existing tunnel, and bending moment induced on the existing tunnel. The stress-transfer mechanism in soil nearby the existing tunnel due to tunnelling is also studied.